A Literature Review: Examining Visual Design and Multimedia Elements Role in Fighting Misinformation and Strengthening Media Trust - Arbi, Hafiz; Juhana, Agus (LPPM STIKI Malang, 2024)
The development of digital media has presented new challenges in maintaining the credibility of information, especially amidst the increasing prevalence of misinformation and hoaxes that spread rapidly through social platforms. This study aims to explore how visual design and multimedia elements can contribute to building audience trust in media and encouraging engagement in disseminating credible information. Using the Systematic Literature Review (SLR) method, the research follows a selection procedure based on PRISMA 2020 guidelines to ensure the validity and quality of the included studies. From 20 articles that meet the inclusion criteria, the key findings indicate that consistent and aesthetically pleasing visual design, particularly those capable of touching the emotional aspects of the audience, plays a crucial role in enhancing media credibility and brand loyalty. Additionally, interactive multimedia approaches, such as dynamic infographics and narrative-based short videos, not only capture audience interest but also strengthen their intention to share credible information. This study concludes that the application of strong visual elements and emotion-based multimedia strategies can help counter misinformation by strengthening media brand equity. Recommendations for future research include developing interactive designs that can educate audiences in identifying credible information and collaborating with media professionals to ensure broader impact. These findings provide practical guidance for media in integrating visual design as an effective tool to build trust and enhance information literacy in the digital age.